Determination of Antiepileptic Drugs Using Dried Saliva Spots. Issue 1 (6th September 2018) - Carvalho, Joana; Rosado, Tiago; Barroso, Mário; Gallardo, Eugenia
Abstract: The present work describes the development and validation of an analytical method for the determination of the antiepileptic drugs (AEDs) phenytoin, phenobarbital, carbamazepine and its active metabolite carbamazepine-10, 11-epoxide, in oral fluid using liquid chromatography coupled to a diode array detector. Correlation between plasma and oral fluid for these compounds has been proven before, making this matrix a great non-invasive alternative for drug-monitoring purposes. The adaptation of cards, commonly applied in dried blood spots (DBS) sampling, to oral fluid resulted in dried saliva spots (DSS). The extraction procedure consisted of applying 50 μL of oral fluid to Whatman TM 903 protein saver cards and drying for 1 h. The extraction was performed with 1 mL of acidified methanol (pH = 5.5) for 5 min with agitation. Afterward, the sample was centrifuged for 15 min at 3, 500 rpm and the supernatant was evaporated and reconstituted with 80 μL of mobile phase. For the AEDs separation, a Zorbax SB-C18 column (1.8 μm, 4.6 × 250 mm i.d.) maintained at 35°C was used, and the mobile phase consisted of 35% acetonitrile and 65% of water:methanol:triethylamine (75.5%:24.2%:0.3%) isocratically with a flow of 0.5 mL/min, and the wavelength was monitored at 210 nm. The method was validated according to internationally accepted criteria, and linearity between 0.1–10 μg/mL was obtained for all AEDs. This is the first method using DSS for the determination of AEDs, showing great potential for routine use in a laboratory for its simplicity, in addition to the advantages inherent to the use of oral fluid as a sample.